Comparison of bacterial community structures in digestive tract between healthy and disease whiteleg shrimp (Litopenaeus vannamei) in Soc Trang, Vietnam - Thanh, Tran Trung; Bott, Nathan; Duc, Le Hoang; Oanh, Dang Thi Hoang; Nam, Nguyen Trung; Ha, Chu Hoang (Vietnam Journal of Biotechnology, 2018)
Gut bacteria comprise a complex bacterial community related to many functions in a host. The stability of gut bacteria plays important models in the health and immunology of a host. Many studies on intestine bacteria constructed via cultivation and Denaturation Gradient Gel Electrophoresis (DDGE) methods have proved a limited efficiency. In order to tackle these drawbacks, the next generation sequencing method was developed on 16S-rRNA-based sequences (Metabarcoding). The composition of bacterial communities was revealed based on the analysis of 16S rRNA sequences of intestine bacteria in Litopenaeus vannamei ponds in comparison with microbial communities in a Penaeus monodon pond and a muscle of shrimp. These results showed that the dominant phyla of intestine bacteria in Litopenaeus vannamei were Proteobacteria (49.3–57.4%), Firmicutes (15.6–34.4%) and Bacteroidetes (0.1–16.9%). Rhizobium(0.4%-26.1%), Vibrio(0–23.9%) and Spongiimonas(0–16,7%) were dominant genera in Litopenaeus vannamei gut. A higher proportion of Fusobacterium (10%), a shrimp pathogen group, was found in a disease shrimp pond (ST4) in comparison with a low growth shrimp pond (ST3) (0%) and a healthy shrimp pond (ST1) (0.6%). Vibrio was marked as shrimp pathogen genus accounted for 22.3% of total genera in ST4 in comparison with 2.4% in ST3 and 3.5% in ST1. Interestingly, a higher percentage of Vibrio rotiferianus (7.98%) was found in ST4 compared to ST3 (1%) and ST1 (0%). Fusobacterium and Vibrio will be the objects for the next experiments to discover shrimp pathogens specifically.